2016
DOI: 10.1111/gfs.12253
|View full text |Cite
|
Sign up to set email alerts
|

Re‐ensiling and inoculant application with Lactobacillus plantarum and Propionibacterium acidipropionici on sorghum silages

Abstract: Re-ensiling of previously ensiled forage has been a common practice in Brazil, and the use of inoculants may provide a means of reducing dry-matter (DM) loss. This study aimed to determine the effect of reensiling and the use of microbial inoculants on the quality of sorghum silage. Treatments were presence/ absence of an inoculant (Lactobacillus plantarum and Propionibacterium acidipropionici) in the silage, and the re-ensiling, or not, of the material after 24 h of exposure to air, and these were tested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 25 publications
3
37
2
5
Order By: Relevance
“…The remaining silage will be available to feed cattle after the silo is opened; therefore, strategies to increase DM recovery are crucial to reduce production costs and avoid silage deficit. The DM recovered in this trial was of 90.3%, higher than that reported by Michel et al (2016) of 83% for sorghum silages re-ensiled after 24 h of air exposure. According to the results, fermentation occurs even in the material that has already fermented during the first ensilage.…”
Section: ( )contrasting
confidence: 68%
See 3 more Smart Citations
“…The remaining silage will be available to feed cattle after the silo is opened; therefore, strategies to increase DM recovery are crucial to reduce production costs and avoid silage deficit. The DM recovered in this trial was of 90.3%, higher than that reported by Michel et al (2016) of 83% for sorghum silages re-ensiled after 24 h of air exposure. According to the results, fermentation occurs even in the material that has already fermented during the first ensilage.…”
Section: ( )contrasting
confidence: 68%
“…Silage compaction can remove water from plant cells, resulting in effluent production, as observed in this experiment. Michel et al (2016) also observed an effluent production of 4% of the OM, after reensiling of untreated sorghum. It is important to highlight that the DM losses found here were significant during re-ensiling, and they should be considered in such conservation process, even when silage is exposed rapidly to air before re-ensiling (e.g., zero time).…”
Section: ( )mentioning
confidence: 73%
See 2 more Smart Citations
“…This may have been due to the low pH of silages (Table 1), as P. acidipropionici bacteria are intolerant to acidic conditions (at a value close to or below 4). Therefore, a silage pH below 4.2 may have inhibited bacterial growth and propionic acid production (Michel et al, 2017). Siqueira et al (2011) evaluated fresh sugarcane silage (without burning) and burned with calcium oxide (CaO) and / or L. buchneri, and observed an NDF content of 75.9 % for sugarcane silage with added L. buchneri at 60 days of fermentation, which was higher than the content of the material before ensiling.…”
Section: Resultsmentioning
confidence: 99%